Investigating linguistic patterns of ideological persuasion and emotional framing in the Albanian political discourse - Qafzezi, Eriola (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2025)
Political discourse serves as a powerful tool for shaping public perception, reinforcing ideological narratives, and legitimizing power structures. This study explores mechanisms of persuasion and propaganda in Albanian political rhetoric, focusing on how loaded language and other discursive strategies contribute to ideological persuasion in media representation. Using Corpus-Assisted Critical Discourse Analysis (CADS), this research examines two speeches delivered by Edi Rama, Prime Minister of Albania, to Albanian diaspora communities in Greece and Italy. The study analyzes linguistic patterns that reinforce inclusion/exclusion, national identity, and political legitimacy in both speeches. The findings demonstrate how linguistic choices amplify persuasion techniques in the public sphere. This research contributes to broader discussions on propaganda, ideological control, and media discourse, offering insights into strategic linguistic conduct in political communication.